If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2h + 7) = 0 Reorder the terms: 3(7 + 2h) = 0 (7 * 3 + 2h * 3) = 0 (21 + 6h) = 0 Solving 21 + 6h = 0 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-21' to each side of the equation. 21 + -21 + 6h = 0 + -21 Combine like terms: 21 + -21 = 0 0 + 6h = 0 + -21 6h = 0 + -21 Combine like terms: 0 + -21 = -21 6h = -21 Divide each side by '6'. h = -3.5 Simplifying h = -3.5
| 1-7w=-6w-9 | | 7b+3=6 | | 4x(y)/4x | | P+35=17 | | 2x-2=5x-13 | | 1-7w=6w-9 | | T+44=-t-6 | | 4xy/4x | | -6+6p=8+8p | | 11y+7w-8w-4y= | | 10x+30-9x+4=x-5+3 | | -10h=-4h+6 | | 1/2-2x/3=3/4-4x/3 | | -d-6=d+90 | | B-21=-11 | | E^4x=e^5 | | -10h=4h+6 | | 2x+11.2= | | -6+4c=5c | | -8-5r=-9r | | 12x-12=6x+24 | | 10x+30-9x+4=x-5-3 | | -n-9=n+45 | | 12x-4y+6x-13y= | | 6x+2(5-4x)=12 | | 8-3t=2t | | x+34=x-8 | | -4.8f=-12.88 | | x^6-343= | | 4a=-10+9s | | X+45-10=x | | 5x-25=3x+19 |